A Method Based on Bottleneck-Linear Assignment for Forming Complex Transport Formations. (20th January 2016) - Xu, Wang-Bao; Rong, Gen-Xi; Liu, Xiao-Ping; Huang, Tian-Yun; Chen, Xue-Bo
Cooperative transportation using multi-robots is a significant challenge in robotics. For the problem, each robot is required, in general, to reach a different task-point to form a transport formation, where all the task-points are determined according to the shape of the transported object and the number of robots. A method based on bottleneck-linear assignment is proposed to form complex transport formations. First, the optimal paths from each robot to all the task-points are calculated by a two-direction path algorithm, which is developed in this paper as the core of the task-points' assignment. Second, in order to optimize the travelling paths of the robots and the time taken to establish the formation, a bottleneck-linear assignment strategy is presented to assign the task-points for the robots. Finally, an improved artificial moment motion controller makes each robot move along a sub-optimal path to reach its task-point. Simulations indicate that the proposed method is feasible and efficient.